Pertanggungjawaban Pidana Partai Politik dalam Perspektif Good Governance dan Hukum Pidana Indonesia - Retno Kusumawiranti; Emy Wahyuningtyas; Hartanto Hartanto (Indonesian Journal Publisher, 2025)
This study aims to analyze the legal foundation and urgency of implementing criminal liability for political parties in Indonesia within the framework of good governance and the rule of law. In Indonesia’s democratic system, political parties play a crucial role in articulating public interests and shaping state policies through the selection and nomination of their members for legislative and executive positions. However, this strategic role also raises fundamental questions regarding legal accountability when political parties or their members engage in criminal acts under the party’s name. The study employs a normative juridical method using statutory, doctrinal, and principle-based approaches to examine the applicability of criminal liability principles to political parties as corporate entities. The findings reveal that although Indonesia’s positive law provides a basis for holding political parties criminally liable, its enforcement remains largely theoretical and lacks effective mechanisms. The doctrines of strict liability and vicarious liability have not yet been consistently applied to political organizations. The study concludes that reforming criminal law and strengthening ethical and institutional integrity within political parties are essential steps to ensure both legal and moral accountability in reinforcing democratic governance and realizing the constitutional mandate of a just and law-based state.